Biokids: An Innovation for Integration of Naqli and Aqli Knowledge - Mohammed Akhiruddin Ibrahim; Siti Rubaini Mat; Latipah Mohd Noor; Afif Arifin; Nur Suriana Mohd Norizan (Global Academic Excellence, 2024)
Non-Indexed Publication